Combination Therapy in Fibromyalgia - Clayton, A. H.; West, S. G. (Current Pharmaceutical Design, 2006)
Fibromyalgia is an enigmatic medical condition whose specific etiology remains undiscovered but currently plagues five million Americans [1]. Research indicates that the origin of the disease is most likely multifactorial. Treatment should therefore be tailored accordingly. Thus, it is often necessary to combine different options in order to achieve the maximum benefit in patients suffering from fibromyalgia.
Keywords: Treatment